In Vitro Co-Culture Interaction Of Adiposederived Mesenchymal Stem Cells (Admscs) And The Effects Of The Secreted Exosomal Mirnas On Mcf7 And Mda-Mb-231 Dormancy - Norlaily, Mohd Ali (2021)
Breast cancer is the most often diagnosed cancer in women worldwide, and it remains a major health challenge due to cancer relapse. Breast cancer relapses are attributable to the existence of a subpopulation of non-proliferating breast cancer cells that have circulated to other organs and survived chemotherapy. The tumor microenvironment (TME) plays a significant role in driving cancer cells into dormancy and the transition of epithelial-to-mesenchymal (EMT) into aggressive phenotype accountable for cancer-related death. Adiposederived mesenchymal stem cells (ADMSCs) have received attention in cancer research due to their tumor-homing ability, immunoregulatory activity and secretion of exosomes as biomarker carriers of microRNAs. Understanding cell-cell interactions between ADMSCs and breast cancer cells through the lens of exosomal miRNAs is essential in shaping the therapeutic function of ADMSCs in treating breast cancer metastasis and relapse. In this study, two different subtypes of established breast cancer cells line were selected to represent the heterogeneity of breast cancer disease and iii recurrence, with MCF7 being the luminal, hormonal dependent and nonmetastatic while MDA-MB-231 being the basal, hormonal independent and high metastasis. After 48 hours of indirect co-culture, exosomes from the medium of MCF7 and MDA-MB-231 breast cancer cells with ADMSCs were extracted. The extravesical exosomes secreted during the cellular interaction carry many biomolecules, including miRNAs that can contribute to breast cancer tumorigenesis. Thus, we sought to evaluate the proliferation and metastasis changes of selected breast cancer subtypes followed by alteration in miRNAs expression profile via next-generation sequencing (NGS) that contribute to the changes. Co-culture resulted in differential expression of exosomal miRNAs profiles that differentiate MCF7 and MDA-MB-231 subtypes. Also, there is a consensus of miRNAs that co-expressed in both subtypes. Those signature miRNAs regulate essential signaling pathways and induce cell cycle arrest by inhibiting epithelial-to-mesenchymal transition (EMT). The maintenance and induction of epithelial features in both cells resulted in reduced proliferation and metastasis abilities of BCCs and increased drug resistance. In summary, the works presented in this thesis contribute to the understanding of intercellular interaction between ADMSCs and breast cancer subtypes MCF7 and MDA-MB-231 in 2D-indirect co-culture. The study highlights the essential roles of ADMSCs in inducing breast cancer cell arrest through the secretion of consensus miRNAs via exosomes. Furthermore, the study has identified ideal miRNAs biomarker to be tested in pre-clinical and clinical studies prior to be used for screening, treatment and diagnosis in breast cancer relapse patients.